Efektifitas Penggunaan Inverted Labial Bow pada Maloklusi Kelas III Skeletal (Laporan Kasus) - Nelvi Yohana; Siti Bahirrah (Andalas Dental Journal, 2020)
The prevalence of Class III malocclusion in the Asian population is between 9% to 19%. Early treatment for Class III malocclusion can be done with some modified intervention on the growth stage. The inverted labial bow appliance was applied on Class III malocclusion patient in growth period show an effective result. The study showed the effectiveness of inverted labial bow appliance on Class III malocclusion. A 9 years 4 months old girl patient came with unaesthetic problem. Lateral cephalometric examination revealed a skeletal Class III malocclusion (ANB -1°, Wits appraisal -8 mm). Removable orthodontic appliance with inverted labial bow and expansion screw was applied on the maxilla of this patient. The treatment was carried out for 9 months. The result of this treatment was skeletal Class I (ANB 2°, Wits appraisal -4 mm). This procedure was simple and effective to correct the skeletal Class III malocclusion on growth stage patient.